A Corpus-Based Analysis of V2 Variation in West Flemish and French Flemish Dialects. Issue 1 (15th February 2019) - Lybaert, Chloé; De Clerck, Bernard; Saelens, Jorien; De Cuypere, Ludovic
Abstract : This paper explores V2 variation in West Flemish and French Flemish dialects of Dutch based on an extensive corpus of authentic spoken data. After taking stock of the existing literature, we probe into the effect of region, prosodic integration, form and function of the topicalized constituent, form of the subject, and the number of constituents in the prefield on (non)inverted word order. This is the first study that carries out regression analysis on the combined impact of these variables in the entire West Flemish and French Flemish region, with additional visualization of effect sizes. The results show that noninversion is generally more widespread than originally anticipated, with unexpected higher occurrence of noninversion in continental West Flemish and lower frequencies in western West Flemish. With the exception of the variable number of constituents in the prefield, all other variables had a significant impact on word order: Clausal topicalized elements, elements that have peripheral functions, and elements that lack prosodic integration all favor noninverted word order. The form of the subject also impacted word order, but its effect is sometimes overruled by discourse considerations.